Computed tomography to identify risk factors for left circumflex artery injury during mitral surgery. (15th October 2021) - Kishimoto, Noriaki; Takahashi, Yosuke; Fujii, Hiromichi; Sakon, Yoshito; Izuta, Shinichiro; Kitada, Ryoko; Morisaki, Akimasa; Yoshida, Hisako; Ehara, Shoichi; Shibata, Toshihiko
Abstract:  : OBJECTIVES: Cases in which the left circumflex coronary artery (LCX) runs close to the mitral annulus are considered high risk for LCX injury during mitral surgery. We investigated the anatomical relationship between the LCX and the mitral annulus using 3-dimensional (3D) computed tomography (CT). METHODS: We constructed 3D-CT images of the LCX and the mitral annulus before surgery in 122 patients with mitral regurgitation (MR). We classified coronary dominance by 3D-CT and MR aetiologies (degenerative, atrial functional MR, ventricular functional MR and Barlow's disease) using echocardiography. We detected the point on the mitral annulus closest to the LCX (X point) and measured the minimum distance from the LCX to the mitral annulus (mCAD). We judged whether atrioventricular disjunction existed using CT. We also investigated the factors affecting mCAD and examined how coronary dominance and MR aetiologies relate to the location of the X point. RESULTS: The median mCAD was 4.2 mm (range 0.9–11.4 mm). Considering coronary dominance and MR aetiologies, mCAD was shorter in patients with left coronary dominance and Barlow's disease. The X point mostly existed on the lateral side of the posterior annulus, but it sometimes existed on the medial side. Multiple regression revealed left dominance and mitral annular disjunction as significant factors affecting mCAD ( P  =   0.01). CONCLUSIONS: The anatomical relationship between the LCX and the mitral annulus can be recognized using superimposed 3D-CT images. This approach is useful to avoid LCX injury in mitral valve surgery since the X point varies between patients. Abstract : The left circumflex coronary artery (LCX) runs around the mitral annulus.